PERTANGGUNGJAWABAN PIDANA BAGI ANAK SEBAGAI PELAKU TURUT SERTA DALAM TINDAK PIDANA PERDAGANGAN ORANG - Nadila Eriska (2021)
Children are the most vulnerable subjects both as juveniles and victims in a crime. The most prominent crime in recent times is the human trafficking, which mainly targets children and women. However, in several cases it was found that apart from the child who has the victim, the juvenile who contributed to help the crime, one of them was a child. Children as juveniles in the criminal trafficking must provide responsibility for a criminal case that has occurred. However, in the process of criminal responsibility by children, they must still pay attention to the legal protection for children. This research aims to examine laws and regulations and cases relating to children as juvenile of criminal trafficking so that a legal argument can be concluded. This research was conducted using normative legal research methods. The main data source used in this research is secondary data applying the statute approach and case approach.